Penerapan Algoritma FIFO Untuk System Pemesanan Kaos Sablon - Ilham Rizky Widianto; Wowon Priatna; Hendarman Lubis (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
The purpose of this study is to solve the problem of screen-printing T-shirt shops. For manual screen printing t-shirt shops, customers often have to visit the store in person or contact them via chat or phone, often encountering the following issues when ordering t-shirts: B. Irregular orders for those who have placed an order in advance or who have been waiting for a long time. One way to solve the queuing problem is the FIFO algorithm. FIFO algorithms are methods for organizing, processing, and manipulating basic data structures in computer systems. The FIFO algorithm phases in this study begin with the data preparation phase, the Gantt cart process, and finally his FIFO wait time. The result of the FIFO stage translates into creating applications using the Java programming language, Android Studio, and the FireBase database. The results of this study can be applied to his FIFO algorithm for customer queues in ordering T-shirts. A t-shirt ordering application was tested using the white box method by running the test case in four passes. All tests passed, so you can use the ordering application based on the FIFO algorithm.